Forest plantations influence on the thermophysical properties of southern chernozems - V. A. Gorban; N. A. Bilova (Вісник Харківського національного університету імені В.Н. Каразіна: Серія Екологія)
Purpose. Evaluation of the influence of Robinia pseudoacacia L. and Quercus robur L. forest plantations on thermal diffusivity, specific heat and thermal conductivity of southern chernozems.